Wide Load Range, High Current Accuracy Low Drop-Out Regulator With Load Tracking Compensation and Dual Soft-Start for Wireless Charging System - Jae Bin Kim; Ji Hoon Song; Sang Sun Yoo; Seok Kee Kim; Yeon Jae Jung; Young Gun Pu; Kang Yoon Lee (IEEE Access)
This study introduces a High Voltage Low Dropout (LDO) regulator featuring a dual soft-start mechanism and load tracking compensation technique for Wireless Power Transfer (WPT) systems. The LDO design efficiently handles a broad input voltage spectrum from 5.15V to 20V and maintains stable performance under fluctuating load conditions ranging from 1mA to 1A. A notable advancement in this design is the dual soft-start mechanism, which enhances startup stability by separately regulating the pass transistor gate and the error amplifier input. Additionally, the load tracking compensation technique optimizes phase margin across diverse load currents, enhancing transient response and output stability. The regulator incorporates a current-sensing circuit for instantaneous overcurrent protection, accommodating load currents between 100mA and 1A. An integrated charge pump expands the error amplifier’s operational range, allowing high-voltage compatibility while running on a 5V supply. Utilizing a BCD process, the proposed circuit delivers high power efficiency and robust performance within a compact layout measuring 0.8814 mm2. These design features contribute to enhanced reliability and efficiency in WPT systems.